MUTUAL RELATIONS OF COMMUNITIES OF SOUTH-WESTERN DAGESTAN WITH GEORGIA AND THE RUSSIAN EMPIRE IN THE SECOND HALF OF THE 18th - EARLY 19th CENTURY - Abdulmazidov, Ramazan Sultanovic (History, Archeology and Ethnography of the Caucasus, 2019)
The present article reveals the history of relations between the south-western unions of communities of Dagestan and the Kingdom of Kakheti in the second half of the 18th - early 19th century. It is established that political and economic contacts between them, due to mutual cooperation, were generally of a peaceful and good-neighbourly nature. In the second half of the 18th century there was a significant strengthening of military-political and cultural ties between Georgia and Dagestan. The arrival of the Russian Empire in the Caucasus in the early 19th century not only shifted the balance of military and political forces in the region, but also radically changed the nature of trade and economic relations between Dagestan and Georgia. In this regard, the main attention is paid to the processes that began after the loss of Georgian statehood, when the border Dagestan communities tried to negotiate with the new authorities. Furthermore, the author reveals the policy of Dagestan feudal rulers, whom the unions of Dagestan communities saw as intermediaries in their relations with the Russian Empire. On the basis of numerous sources, both already published and identified by the author in the Central historical archive of Georgia, the article considers the most important events that took place in the region during the study period. According to the author, before the appointment of A. P. Ermolov to the Caucasus, St. Petersburg did not rush to assert its power there, content at first with "external signs of citizenship" of the highlanders. With the arrival of the latter, who pursued the policy on the well-known principle of "divide and conquer", the trade and economic blockade of the highlanders of Western Dagestan increased significantly, leading to their subsequent active participation in the people’s liberation movement of the highlanders of the North-East Caucasus in the 20-50s’ of the 19th century. .